Added Value of Preoperative Computed Tomography for Determining Cartilage Degeneration in Patients With Osteochondral Lesions of the Talar Dome. Issue 1 (January 2018) - Nakasa, Tomoyuki; Ikuta, Yasunari; Yoshikawa, Masahiro; Sawa, Mikiya; Tsuyuguchi, Yusuke; Adachi, Nobuo
Background: Osteochondral lesions of the talar dome (OLTs) involve the articular cartilage and subchondral bone. The subchondral bone plate (SBP) plays a crucial role in cartilage metabolism, and computed tomography (CT) can provide more precise information on subchondral bone. CT image prediction of the histological findings on OLT will be useful to determine the most appropriate therapeutic strategy. Purpose: To evaluate the unique features of the CT findings that relate to the condition of the articular cartilage in OLT. Study Design: Cohort study; Level of evidence, 3. Methods: Thirty ankles in 29 patients who had OLT with an osteochondral fragment were retrospectively reviewed. At surgery, the osteochondral fragment of 19 ankles could be preserved (preservation group) by fixation or drilling, and in the remaining 11 ankles, the osteochondral fragment was removed (excision group). Preoperative CT findings were compared between the 2 groups. Biopsies of the osteochondral fragment from 13 ankles were performed. The relationship between the CT and histological findings were evaluated. Results: The area of lesion in the preservation group was significantly larger than that in the excision group. The CT images of the lesion showed the rate of absorption of the SBP in the preservation group to be lower than that in the excision group. As for the lesion bed absorption, it was higher in the preservation group than in the excision group. All cases in the excision group showed bed sclerosis, compared with 42.1% in the preservation group. The specimens with disruption of the SBP exhibited cartilage degeneration and abundant chondrocyte cloning. OLT with absorption of the SBP on CT showed severe cartilage degeneration, while the remaining SBP on CT showed low-grade cartilage degeneration. Conclusion: This study shows the features of preoperative CT and histological findings in OLT with osteochondral fragments. The condition of the SBP affects the cartilage degeneration. CT findings provide important information for the determination of surgical treatment.